Evaluation Criteria for Interactive E-Books for Open and Distance Learning - Bozkurt, Aras; Bozkaya, Mujgan (International Review of Research in Open and Distributed Learning, 2015)
The aim of this mixed method study is to identify evaluation criteria for interactive e-books. To find answers for the research questions of the study, both quantitative and qualitative data were collected through a four-round Delphi study with a panel consisting of 30 experts. After that, a total of 20 interactive e-books were examined with heuristic inquiry methodology. In the final phase, the results of the Delphi technique and the heuristic inquiry results were integrated. As a result, four themes, 15 dimensions, and 37 criteria were developed for interactive e-books. Lastly, the results and their implications are discussed in this paper and suggestions for further research are presented.